2021
DOI: 10.3389/fpsyg.2021.628355
|View full text |Cite
|
Sign up to set email alerts
|

Interoception Disorder and Insular Cortex Abnormalities in Schizophrenia: A New Perspective Between Psychoanalysis and Neuroscience

Abstract: The existence of disturbances in the perception of somatic states and in the representation of the body with the presence of cœnesthetic hallucinations, of delusional hypochondriac ideas or of dysmorphophobias is a recognized fact in the psychopathology of schizophrenia. Freudian psychoanalytic theory had accorded a privileged place to the alteration of the perception of the body in schizophrenia. Freud had attributed to these phenomena a primary and prodromal role in the psychopathology of psychosis. We propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In their review, Wylie and Tregellas [ 127 ] discuss the hypothesis that deficits in recognizing emotions in faces, in pain perception, and in the attribution of sensory percepts are related to dysfunctions in the insula in SZP. Recently, several authors [ 158 , 159 , 160 , 161 ] reviewed the relationship between insular and cognitive impairment and interoception in SZP. In light of these literature findings, it is conceivable that activation of the binding system due to pre-existing dysfunctions in the insula leads to hyperactivation of the insula, as is also found in auditory hallucinations [ 162 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their review, Wylie and Tregellas [ 127 ] discuss the hypothesis that deficits in recognizing emotions in faces, in pain perception, and in the attribution of sensory percepts are related to dysfunctions in the insula in SZP. Recently, several authors [ 158 , 159 , 160 , 161 ] reviewed the relationship between insular and cognitive impairment and interoception in SZP. In light of these literature findings, it is conceivable that activation of the binding system due to pre-existing dysfunctions in the insula leads to hyperactivation of the insula, as is also found in auditory hallucinations [ 162 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we observe that psychoanalysis and the neurosciences agree when it comes to the observation that some representations–particularly those stemming from our experiences with the environment, which are stored in our autobiographical memory–can work as a medium for the binding function. These representations take on, in combination with traces from somatic states, a homeostatic role in the psychic balance and are generators of a form of mental equilibrium (Freud, 1900 ; Ansermet and Magistretti, 2004 , 2010 ; Tran The et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, areas of the DMN such as the ACC are dysfunctional in schizophrenia, and these anomalies have also been linked to disfunctions in the anterior insula (Carter et al, 2001 ). Furthermore, the data from neurobiological literature on anomalies of the insular cortex in schizophrenia, have demonstrated that the disfunction of the insula can constitute one of the underlying biological causes of the disorders in corporal perception present in schizophrenia (Tran The et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to promising future implications of working on the interoceptive awareness of individuals with clinically diagnosed conditions. It is important to note that insular abnormalities manifest differently in various clinical disorders, which calls for further research in how interoceptive awareness differs within specific conditions [ 74 ].…”
Section: Time Perception In Clinical Conditionsmentioning
confidence: 99%
“…The authors made it clear that temporal dysfunctions are part of the psychopathology of schizophrenia and that concentrating more on the time processing dysfunction in the illness, could be key to improving cognition and functioning in this population [ 75 ]. Moreover, schizophrenic patients also experience grave alterations to the sensitivity of their internal body signals, again pointing towards the role of insular dysfunction in the disturbance of both interoception and time perception [ 74 ].…”
Section: Time Perception In Clinical Conditionsmentioning
confidence: 99%